2012
DOI: 10.7314/apjcp.2012.13.12.6269
|View full text |Cite
|
Sign up to set email alerts
|

SNPs of Excision Repair Cross Complementing Group 5 and Gastric Cancer Risk in Chinese Populations

Abstract: We conducted a case-control study to determine the association between several potential SNPs of excision repair cross complementing group 5 (XPG) and gastric cancer susceptibility, and roles of XPG polymorphisms in combination with H.pylori infection in determining risk of gastric cancer. In our study, we collected 337 newly diagnosed gastric cancer cases and 347 health controls. Three SNPs of XPG, rs2296147T>C, rs2094258C>T and rs873601G>A, were genotyped using the Taqman real-time PCR method with a 7900 HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 25 publications
1
34
1
Order By: Relevance
“…Several previous studies have reported the association between XPG gene polymorphisms and development of gastric cancer (Hussain et al, 2009;Duan et al, 2012;He et al, 2012;Yang et al, 2012). He et al (2012) conducted a case-control study with 125 gastric cancer and 1196 cancer-free controls and reported that the XPG polymorphisms may contribute to the risk of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported the association between XPG gene polymorphisms and development of gastric cancer (Hussain et al, 2009;Duan et al, 2012;He et al, 2012;Yang et al, 2012). He et al (2012) conducted a case-control study with 125 gastric cancer and 1196 cancer-free controls and reported that the XPG polymorphisms may contribute to the risk of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the association between ERCC5rs2094258 and rs751402 polymorphisms and the development of certain malignancies, including breast and gastric cancers, salivary gland tumors, and oral squamous cell carcinoma (Duan et al, 2012;Yang et al, 2012;Zavras et al, 2012;Meng et al, 2013;Na et al, 2015;Wang et al, 2015). For instance, Duan et al (2012) and Yang et al (2012) both reported that these polymorphisms contribute to the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al (2012) conducted an investigation into the association between these two ERCC5 promoter SNPs and gastric cancer in a Chinese population, concluding that rs751402 does affect the risk of developing this malignancy. In another Chinese study of 337 newly diagnosed gastric cancer cases and 347 healthy controls, Yang et al (2012) found that rs2094258 is associated with increased risk of this disease. However, in the present work, we failed to establish an association between ERCC5 rs2094258 and rs751402 polymorphisms and development of gastric cancer among Chinese patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations